2018
DOI: 10.11606/s1518-8787.2018052000373
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of natural birth and elective C-section in supplemental health

Abstract: OBJECTIVE To conduct a cost-effectiveness analysis of natural childbirth and elective C-section for normal risk pregnant women.METHODS The study was conducted from the perspective of supplemental health, a health subsystem that finances private obstetric care, represented in Brazil by health plan operators. The reference populations were normal risk pregnant women, who could undergo natural childbirth or elective C-section, subdivided into primiparous and multiparous women with previous uterine scar. A decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
0
15
1
7
Order By: Relevance
“…Promoting vaginal deliveries is also cost-beneficial since a recent analysis performed in Brazil showed that natural childbirth was more cost-effective than elective CS for primiparous normal risk pregnant women. This conclusion did not apply, however, for multiparous women with previous uterine scar [23]. Compared to a previous investigation performed in 2017 in our clinic, which revealed that young women were more likely to give birth by CS at any age group [24], our present results show a modest but encouraging increase in vaginal delivery rates among teenagers.…”
Section: Discussioncontrasting
confidence: 99%
“…Promoting vaginal deliveries is also cost-beneficial since a recent analysis performed in Brazil showed that natural childbirth was more cost-effective than elective CS for primiparous normal risk pregnant women. This conclusion did not apply, however, for multiparous women with previous uterine scar [23]. Compared to a previous investigation performed in 2017 in our clinic, which revealed that young women were more likely to give birth by CS at any age group [24], our present results show a modest but encouraging increase in vaginal delivery rates among teenagers.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the length of hospital stay has been proven to have a large impact on overall hospital costs, with the cost of a 36 h postnatal stay for a mother in the United Kingdom averaging £692 56 . Similarly, a study completed in the United States showed the average daily cost for postnatal stay being $544.65 57 . Decreasing the length of hospital stay would significantly decrease the hospital cost per mother.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, the mean and standard deviation of the total cost for natural delivery and cesarean section were 26980930.90±16603206.35 and 6126709.15±48883938.59, respectively. In the research of Alain Pivozan Intriger and her colleagues, it was observed that natural delivery was less expensive for primiparous pregnant women compared to elective cesarean section ($5,210.96 versus $5,753.54) (29). An increase in cesarean delivery increases direct payments and out-of-pocket costs and dramatically undermines the sustainability of health care systems.…”
Section: Discussionmentioning
confidence: 99%